2014
DOI: 10.1080/13670050.2013.878304
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual spelling patterns in middle school: it is more than transfer

Abstract: This study examined the Spanish and English spelling patterns of bilingual adolescents, including the cross-linguistic effects of each language, by applying a fine-grained measure to the differences in spelling in naturalistic writing. Spelling errors were taken from narrative and expository writing samples provided by 20 Spanish-English bilingual adolescents (n = 160). Errors were coded by categories (phonological, orthographic, and morphological) and specific linguistic features affected and then analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 23 publications
5
29
0
Order By: Relevance
“…Unlike Bahr et al. (), Howard and her colleagues found that cross‐linguistic spelling errors were nonexistent by fourth grade. Spelling errors made at an early age had no effect on the students’ literacy development beyond second grade.…”
Section: Development Of Bilingual Orthographymentioning
confidence: 73%
See 4 more Smart Citations
“…Unlike Bahr et al. (), Howard and her colleagues found that cross‐linguistic spelling errors were nonexistent by fourth grade. Spelling errors made at an early age had no effect on the students’ literacy development beyond second grade.…”
Section: Development Of Bilingual Orthographymentioning
confidence: 73%
“…In a comparison of dual language programs, Howard et al (2012) concluded that overall biliteracy is not dependent on a person's ability to spell correctly in the early years of development. Unlike Bahr et al (2015), Howard and her colleagues found that cross-linguistic spelling errors were nonexistent by fourth grade. Spelling errors made at an early age had no effect on the students' literacy development beyond second grade.…”
Section: Development Of Bilingual Orthographymentioning
confidence: 97%
See 3 more Smart Citations